Effect of Proline and Aspirin on Seed Germination and Seedling Growth of Lycopersicon esculentum and Surface Growth of Fusarium oxysporum - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
Research was conducted to study the effect of proline and aspirin with 10 and 20 ppm on seed germination and seedling growth of Lycopersicon esculentum and the effect of surface growth of Fusarium oxysporum. The results showed that the proline and aspirin effected significantly to decreased percentage of seed germination, acceleration of germination, promoter indicator, elongation speed of radical and plumule and also the infection percentage of seed decay and surface growth of Fusarium oxysporum was reduced significantly.